2020
DOI: 10.1161/circulationaha.120.048739
|View full text |Cite|
|
Sign up to set email alerts
|

Renal and Cardiovascular Effects of SGLT2 Inhibition in Combination With Loop Diuretics in Patients With Type 2 Diabetes and Chronic Heart Failure

Abstract: Background: Sodium-Glucose Co-Transporter-2 (SGLT2) inhibitors improve heart failure (HF) associated-outcomes in patients with type 2 diabetes (T2D). In patients with HF, SGLT2 inhibitors will likely be co-prescribed with a loop diuretic, but this combined effect is not well-defined. Our aim was to assess the diuretic and natriuretic effect of empagliflozin in combination with loop diuretics. Methods: The RECEDE-CHF trial (NCT03226457) was a randomized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
105
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(123 citation statements)
references
References 30 publications
3
105
1
Order By: Relevance
“…Treatment with SGLT2 inhibitors increases glucose concentration in the distal nephron, resulting in a decrease in the osmotic gradient between the tubular fluid and interstitium. This reduces passive water reabsorption, resulting in osmotic diuresis ( 13 , 14 ). In the current study, glycosuria was consistently increased, although we did not observe a clear effect on urine volume, which contrasts the findings from in silico models ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with SGLT2 inhibitors increases glucose concentration in the distal nephron, resulting in a decrease in the osmotic gradient between the tubular fluid and interstitium. This reduces passive water reabsorption, resulting in osmotic diuresis ( 13 , 14 ). In the current study, glycosuria was consistently increased, although we did not observe a clear effect on urine volume, which contrasts the findings from in silico models ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of varying designs in healthy volunteers or patients with type 2 diabetes have indeed suggested that SGLT2 inhibitors cause transient increases in 24-h sodium excretion ( 8 11 ) along with reductions in plasma and extracellular volume ( 12 , 13 ). Studies in patients with heart failure showed either no change ( 14 ) or a modest increase in sodium excretion in parallel with a reduction in plasma volume ( 15 ). The prior studies were limited by the fact that sodium excretion was estimated from spot urine samples instead of 24-h urine collections, or dietary intake of sodium was not recorded or standardized.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 21 RCTs [ 10 , 24 , 25 , 29 31 , 33 , 39 52 ] were recognized eligible in this meta-analysis, including 3 in crossover design [ 41 , 44 , 50 ]. A total of 10,978 participants were enrolled, including 6236 in the SGLT2i group and 4821 in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Seventy percent of the participants were male, and the mean age ranged from 56 to 73 years old. The mean follow-up period ranged from 14 days to one year, including three studies [ 41 , 50 , 51 ] less than 3 months. Participants with T2DM that were mostly in stage A–B HF were enrolled in 10 studies [ 24 , 25 , 39 , 40 , 44 , 46 , 48 , 49 , 51 , 52 ], and patients with T2DM and stage C HF were enrolled in 11 studies [ 10 , 29 31 , 33 , 41 – 43 , 45 , 47 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation